Disruption of CDK5 regulatory subunit 1, p35, limits immunosuppressive M2 macrophages while maintaining functional M1 macrophages - Zampieri, Juliana R.; Choi, Sung Hee; Myers, Jay T.; Tomchuck, Suzanne L.; Eid, Saada; Askew, David; Huang, Alex Y. (Frontiers in Immunology, 2025)
IntroductionMacrophage polarization into M1 or M2 phenotypes is a complex process influenced by various factors. However, existing literature and ongoing research support the view that Cyclin-Dependent Kinase 5 (CDK5) may play an important role in this process. CDK5 is a protein kinase that requires association with regulatory, co-activating proteins, p35 (CDK5R1) or p39 (CDK5R2), for functional activation.PurposeThis study investigated the role of the p35 protein in regulating M1 and M2 polarization.MethodsWe compared bone marrow derived macrophages from wild type (WT) and p35 knockout (KO) mice under both M1 (IFNγ + LPS) and M2 (IL4) conditions, differentiated with M-CSF or GM-CSF. The expression of surface markers (CD86, CD206), enzyme expression (Arginase-1 and iNOS), metabolism and antigen process and presentation were compared.ResultsWhile p35 had modest effect on phenotype during M1 or M2 polarization, p35 expression was important for Arginase1 induction after M2 polarization. The absence of p35 significantly increased glycolysis during M1 polarization, while it also enhanced mitochondrial oxidative phosphorylation in the context of M2 polarization. While p35 was important for antigen processing by M0 and M2, M1 were able to maintain capacity to process antigen albeit with a reduction due to decreased stability of peptide: MHC II complex.ConclusionWhile loss of p35 resulted in minor changes in phenotype, there were decreases in ARG-1 production and STAT3 phosphorylation, increased metabolism, and dramatically reduced antigen processing by M0, M1 or M2. The absence of p35 enhanced antigen uptake, but it had no effect on degradation of antigen, suggesting an inability to produce peptide: MHC II complexes in the absence of p35 in M0 and M2. In contrast, p35-deficient M1 maintained an ability to rapidly produce peptide: MHC II complexes but showed a reduction in the stability of these complexes on the surface. Our findings reveal a crucial role for p35 in regulating macrophage metabolism and antigen function, with implications for the development of novel therapeutic strategies.